Real‐world comparative analysis of bleeding complications and health‐related quality of life in patients with haemophilia A and haemophilia B. Issue 5 (9th August 2018) - Booth, Jason; Oladapo, Abiola; Walsh, Shaun; O'Hara, Jamie; Carroll, Liz; Garcia Diego, Daniel‐Anibal; O'Mahony, Brian
Abstract : Introduction: Clinical severity and impact of haemophilia on quality of life have been generally considered to be lower for haemophilia B (HB) compared with haemophilia A (HA) patients. Aims: To compare annual bleeding rate (ABR), target joint development and health‐related quality of life (HRQoL) between adult (≥18 years) severe HA and HB patients using recent data from the Cost of Haemophilia in Europe: a Socioeconomic Survey (CHESS) study. Methods: Multivariate generalized linear models (GLM) were constructed to assess the relationship between haemophilia type, ABR, HRQoL (derived from EQ‐5D index scores) and the presence of target joints while controlling for covariates. Results: Of the 1225 patients included, 77% (n = 949) had HA and 23% (n = 278) had HB. Of the 514 patients who completed the EQ‐5D, 78% (n = 405) had HA, and 22% (n = 110) had HB. Unadjusted mean ABR was 3.79 in HA and 4.60 in HB. The presence of ≥1 target joint was reported in 59% and 54% of patients with HA and HB, respectively. Unadjusted mean EQ‐5D index score was 0.78 in HA and 0.76 in HB. Haemophilia type was not a significant predictor of ABR, target joints or HRQoL when adjusted for confounding factors such as BMI, age and replacement therapy regimen. Conclusion: Data suggest comparable ABR, incidence of target joints and HRQoL between patients with HB and HA indicating comparable clinical severity and disease impact on patient quality of life.